The Indian mosaic (Part the second) - Mongush, Marina V. (The New Research of Tuva, 2010)
The second part of the diary of an ethnographer, travelling to India
Keywords: India; Tibet; Tibetans; beauty; contest; Oracle; Buddhism; Dalai Lama; Bogd gegen